Oribatula (Zygoribatula) frisiae - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Oribatula (Zygoribatula) frisiae (Oudemans, 1900) Material – Twenty specimens in Güdül, N 40° 2′ 03.34′′, E 32° 15′ 23.28′′, alt. = 729 m, 20 July 2018, soil with litter in vineyard. Previous records in Turkey – Ankara (Kumral and Cobanoğlu 2016), Kocaeli (Yaça and Baran 2019). Global distribution – Holarctic. Ecology – Forest and urban soils.

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 265, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Arthropoda; Oribatulidae; Arachnida; Animalia; Oribatula frisiae; Biodiversity; Sarcoptiformes; Oribatula; Taxonomy; 15. Life on land